Chemical characteristics, antioxidant capacity, bacterial community, and metabolite composition of mulberry silage ensiling with lactic acid bacteria - Guo, Yaya; Huang, Rongzheng; Niu, Yujie; Zhang, Peng; Li, Yuan; Zhang, Wenju (Frontiers in Microbiology, 2024)
Abstract：Mulberry has high crude protein and biologically active compounds but difficult ensiling due to lack of adequate epiphytic LAB. This study aimed to investigate the effects of inoculation with Lactiplantibacillus plantarum and Pediococcus pentosaceus isolated from mulberry with higher antioxidant capacity alone or combination with Streptococcus bovis on chemical characteristics, antioxidant capacity, bacterial community and metabolites composition of mulberry silage. The results showed that all inoculation groups had higher dry matter and lower pH than control, particularly in LP (DM, 32.03%, pH=4.44) and LP_PP_SB (DM, 31.68% pH=4.26) after 60 days of ensiling. Ammonia nitrogen (AN) content was both lowest in LP_SB and LP_PP_SB , which were 1.86 g/kg FM and 1.05 g/kg FM, respectively, (P < 0.05). Only LP_PP_SB increased polyunsaturated fatty acids (PUFA, 1.2851 g/kg DM, P < 0.05) than control. Ferric reducing antioxidant power (FRAP) values was increased in all inoculation treated groups compared with control (P < 0.05). 2,2-Diphenyl-1-picrylhydrazyl (DDPH), 3ethylbenzothiazoline-6-sulfonic acid (ABTS) and FRAP were exhibited the highest level in LP_PP and LP_PP_SB treated groups. Enterobacter were dominant both in control and SB treated groups, relative abundance was 41.18% and 32.35%, respectively (P < 0.05). Relative abundance of Lactiplantibacillus was higher in LP, LP_PP, and LP_SB (81.84% -82.69%). Relative abundance of Pediococcus was higher in PP, PP_SB, and LP_PP_SB (74.27% -85.27%). Untargeted metabolomics analysis results showed that five flavonoids (apigenin, eriodictyol, quercetin-3-glucoside, rutin, Kaempferol-3-O-rutinoside)were up-regulated in all inoculation groups (expect for SB treated groups). Among them, eriodictyol was both positively correlated with ABTS and FRAP and also showed the highest relative abundance in LP_PP and LP_PP_SB. As far as we know, this study was the first to investigated relationship between inoculants of epiphytic lactic acid bacteria and antioxidant capacity by 16sRNA Illumina sequencing technology and untargeted metabolomics analysis, respectively. Consequently, inoculated L. plantarum, P. pentosaceus alone, respectively, or in combined with S. bovis all increased the relative abundance of Lactiplantibacillus and Pediococcus, decreased the relative abundance of Enterobacter, particularly in LP_PP_SB. And inoculants could increase relative abundance of five flavonoids (apigenin, eriodictyol, quercetin-3-glucoside, rutin, Kaempferol-3-O-rutinoside), especially eriodictyol to improved antioxidant capacity of mulberry silage.